2016
DOI: 10.1039/c6ra02368a
|View full text |Cite
|
Sign up to set email alerts
|

Towards the understanding of non-thermal air plasma action: effects on bacteria and fibroblasts

Abstract: Non-thermal plasma research has put a growing focus on the bacteria inactivation problem. Here we show how non-thermal plasma destroys Gram-positive and Gram-negative bacteria and discuss the mechanisms of plasma bactericidal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Importantly, air NTP produced elevated levels of NO, O 3 and in comparison with He NPT. Contrarily, in He NTP a substantial amount of He ions were detected, which were lacking in air NTP 5, 21 .
Figure 1Physicochemical characterization of the chemically distinct non-thermal plasmasand cytotoxic effects elicited by different plasmas. ( a ) The fourier transform infrared spectroscopy (FT-IR) of air, helium NTPs and ozone.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, air NTP produced elevated levels of NO, O 3 and in comparison with He NPT. Contrarily, in He NTP a substantial amount of He ions were detected, which were lacking in air NTP 5, 21 .
Figure 1Physicochemical characterization of the chemically distinct non-thermal plasmasand cytotoxic effects elicited by different plasmas. ( a ) The fourier transform infrared spectroscopy (FT-IR) of air, helium NTPs and ozone.
…”
Section: Resultsmentioning
confidence: 99%
“…A recent study shows that oxidants and their targets might be spatially confined within the cell 60 . Moreover, we have previously shown that air and He NTPs possess different ion penetration profiles 5, 21 . In addition, the ROS/RNS composition and concentrations range in the plasma-treated liquids are variable, depending on the carrier gas that forms NTP 9, 61 .…”
Section: Discussionmentioning
confidence: 99%
“…During the treatment time Δt = 1 min, the plasma produced a mean ion fluency of 6.4 · 10 14  ions cm −2 . Detailed characteristics of the system have been published previously102728.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously developed and characterized NTP system with controlled plasma composition and working temperature that has been shown to be an effective tool for bacterial eradication2728. In our recent study we demonstrated that chemically distinct plasmas trigger different responses in mammalian cells, and that the extent of biological responses to NTP may grossly differ between phenotypically distinct cell lines27.…”
mentioning
confidence: 99%
“…Increasing evidence suggests that reactive oxygen species (ROS) are the major players in NTAPP-induced apoptosis in vitro 131415. However, there is a discrepancy between the cytotoxic effect of non-thermal plasma and ozone, which is a considerable component of non-thermal air plasma1617.…”
mentioning
confidence: 99%